2009
DOI: 10.1108/17506180910940351
|View full text |Cite
|
Sign up to set email alerts
|

Destination websites' persuasiveness

Abstract: PurposeThe purpose of this research is to help tourism marketers maximize the persuasiveness of their websites toward the objective of increasing visitation to their destination.Design/methodology/approachThe paper describes a two‐part research project: a content analysis of websites to determine the most frequently used elements; and an experiment wherein respondents view one of ten randomly assigned websites and complete a survey about the credibility, message strength, and persuasiveness of that site.Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…The questionnaires were divided into 4 parts: 1) perceived quality of the website (11 empirical indicators); 2) netizen's intention to use the website (6 empirical indicators); 3) online purchase intentions (8 empirical indicators); and 4) netizen's demographic profiles and the internet/social media usage (8 questions). All indicators of each variable was developed based on relevant references and previous research (Loiacono et al, 2002;Lee & Kozar, 2006;Loda et al, 2007;Banerjee, 2008;Chang et al, 2008;Hsu et al, 2015;Hur, et al, 2015). The completed responses from the participants would automatically recorded into a spreadsheet facilitated by Google Drive to allow the researchers saving time for not conducting a manual data editing.…”
Section: E T H O D O L O G Ymentioning
confidence: 99%
“…The questionnaires were divided into 4 parts: 1) perceived quality of the website (11 empirical indicators); 2) netizen's intention to use the website (6 empirical indicators); 3) online purchase intentions (8 empirical indicators); and 4) netizen's demographic profiles and the internet/social media usage (8 questions). All indicators of each variable was developed based on relevant references and previous research (Loiacono et al, 2002;Lee & Kozar, 2006;Loda et al, 2007;Banerjee, 2008;Chang et al, 2008;Hsu et al, 2015;Hur, et al, 2015). The completed responses from the participants would automatically recorded into a spreadsheet facilitated by Google Drive to allow the researchers saving time for not conducting a manual data editing.…”
Section: E T H O D O L O G Ymentioning
confidence: 99%
“…In the tourism context, the concept of credibility assumes a great relevance due to the intangible nature of tourism products that don't allow evaluating before purchase and risks associated with decision making (Loda, Teichmann & Zins, 2009;Ayeh, Au, & Law, 2013) examined travel consumers' perceptions regarding the credibility of user generated contents sources and how such perceptions may influence attitudes and intentions toward UGC utilization for travel planning. This study found the central mediating role of attitude and homophily as a critical determinant of both credibility and attitude.…”
Section: Credibilitymentioning
confidence: 99%
“…Some researchers about the travel websites have focused on analysing the operation of the website in terms of accessibility and content (e.g., Bai et al, 2008; Tang and Jang, 2008; Loda et al, 2009; Woodside et al, 2011; Rodríguez-Molina et al, 2015). Their results have shown that website design and Internet marketing features contribute to an effective delivery of messages, quality of products and services, and brand image.…”
Section: Literature Reviewmentioning
confidence: 99%